Character Education Management Through Intracurricular, Co-curricular, and Extracurricular Activities in Schools - Wulandari, Fitri; Nurbayah, Siti; Saidah, Farichatus; Ulum, M. Zainul (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
Character education in schools is becoming increasingly important in the formation of students' noble values in the complex modern era. However, the implementation of systematic and integrated character education management still faces various challenges in the field, including in the integration of character values into intracurricular, co-curricular, and extracurricular activities. This study aims to explore the implementation of character education management at MAN Kota Pasuruan. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, observation, and documentation. The results show that MAN Kota Pasuruan has succeeded in effectively integrating character values into the curriculum through the Pancasila Rahmatan lil ‘Alamin project, as well as implementing a holistic assessment system that includes cognitive and character aspects of students. This study provides theoretical contributions by strengthening the understanding of the interaction of various approaches to character education, as well as practical recommendations for the development of character education programs in other madrasas. These findings are expected to be a reference for educational institutions in increasing the effectiveness of character education through systematic and collaborative management.